Cybersecurity Risk Detection Based on Roblox User Review Analysis Using TF-IDF and Comparison of Naïve Bayes and Support Vector Machine - Alam, RG Guntur; Ibrahim, Huda (Informatika, Universitas Jenderal Soedirman, 2026)
The rapid growth of online gaming platforms increases user engagement while also exposing users to technical and cybersecurity risks. User reviews represent a rich yet underutilized textual source that can serve as early indicators of such risks. Unlike prior studies focused on sentiment polarity, this study positions user reviews as early cybersecurity risk signals by mapping complaint patterns into operational security risk categories relevant to system developers. This study compares Naïve Bayes (NB) and Support Vector Machine (SVM) in detecting cybersecurity risks from imbalanced textual data derived from Roblox user reviews. A total of 3,000 reviews were collected from the Google Play Store via web scraping and preprocessed using case folding, normalization, tokenization, stopword removal, and stemming. Reviews were classified into four cybersecurity risk categories (account access issues, suspicious behavior, connection instability, and data loss) based on rule-based security keyword mapping. Text representation employed TF-IDF with unigram and bigram features, while class imbalance was handled through undersampling. Model evaluation used three train–test splits (80:20, 70:30, and 60:40) and was assessed using Accuracy, Macro F1-score, AUC-PR, training time, and statistical testing. Results show that SVM consistently outperforms Naïve Bayes, achieving higher accuracy (0.86–0.88) and substantially better Macro F1-scores (0.73–0.77), indicating more balanced detection of minority cybersecurity risks. These differences are statistically significant (p < 0.05). The novelty of this study lies in transforming user reviews into a structured cybersecurity risk detection framework and empirically demonstrating the robustness of SVM in identifying rare but critical risks from imbalanced data.